GLUCOCORTICOID-REGULATED GENE IN TRANSFORMED TO NORMAL PHENOTYPIC REVERSION - Valentini, Sandro Roberto [UNESP]; Oliveira, MLS; Sasahara, R. M.; Armelin, MCS (Associação Brasileira de Divulgação Científica (ABRADIC), 1994)
Glucocorticoid hormones modulate the actions of peptide growth factors and constitute important therapeutic tools as anti-inflammatory and anti-tumor agents. The C6 rat glioma cell line responds to glucocorticoids with changes in morphology and growth block. The hyper-responsive ST1 cell variant displays a dramatic phenotypic reversion under the influence of these hormones. Thus, the transformed and tumorigenic cells reversibly change to a normal and non-tumorigenic phenotype. In addition, the cells also produce a C-type retrovirus. We used poly A(+) mRNA from ST1 cells that had been treated with hydrocortisone to generate a cDNA library that was then screened, by differential hybridization,for glucocorticoid-responsive cellular sequences. The retroviral genomic RNA was used to generate a viral-specific probe. Cross hybridization led to the isolation of at least 4 cDNA clones of which 3 are cellular sequences and one corresponds to a retroviral gene. These clones were characterized by DNA sequencing and Northern blot hybridization analysis.
Keywords: CDNA CLONING; DIFFERENTIAL HYBRIDIZATION; GLUCOCORTICOID-REGULATED GENES